A comparative study of the previous and the new English language textbook: Pre-university book versus Vision 3 (Research Article) - Mavadat Saidi (Journal of English Language Teaching and Learning, 2021)
The current comparative study aimed to juxtapose the newly compiled English textbook for the students in the third grade of senior high school, Vision 3, and the previously taught English textbook for pre-university students. To this end, 130 experienced teachers, with the experience of teaching both textbooks, were asked to complete an eclectic checklist comprising 38 items and evaluating the book in terms of nine major criteria, namely general considerations, vocabulary, grammar, speaking, listening, reading, writing, pronunciation supplementary materials, tasks, and activities. Following that, 20 teachers were interviewed to enrich the results of the quantitative data. Overall, the results revealed the teachers’ contentment with the newly developed English textbook. In particular, the mean values indicated that English teachers rated the speaking and listening sections as the most satisfactory parts while they ranked the supplementary materials criterion as the least satisfactory one in Vision 3. Indeed, they believed that notwithstanding the dramatically positive changes in Vision 3, the book still requires undergoing major revisions to act as a rich source for enabling the EFL students to communicate fluently, accurately, and effectively. In this regard, the findings would benefit the materials developers to locate the areas for further modifications.